2021
DOI: 10.3389/fphys.2021.646721
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Adelphocoris suturalis Jakovlev (Hemiptera: Miridae) Immune Responses to Fungal and Bacterial Pathogens

Abstract: The wide-spread culture of transgenic Bt cotton resisting the infamous cotton bollworms has reduced the adoption of broad-spectrum insecticides to a large extent. Consequently, the non-targeted insect Adelphocoris suturalis Jakovlev has become a major cotton pest in China. Entomopathogenic microbes show promising results for controlling this pest in the future, but A. suturalis innate immune responses to these pathogens are poorly understood. Here, we used the entomopathogenic fungus Beauveria bassiana and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that some symbiotic bacteria help insect hosts form new feeding habits, thus expanding food sources and enhancing the adaptability of insects to the environment ( Lu et al, 2001 ; Douglas, 2009 ), which may also increase the difficulty of A.suturalis control. There are currently few studies examining the symbiotic bacteria of A. suturalis , making the number and species of the symbiotic bacteria in A. suturalis uncertain ( Luo et al, 2021 ; Ma et al, 2021 ). Therefore, it is necessary to investigate the distribution of symbiotic bacteria at different stages of A. suturalis , which will provide a framework for exploring the function of symbiotic bacteria and pest control in A. suturalis .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that some symbiotic bacteria help insect hosts form new feeding habits, thus expanding food sources and enhancing the adaptability of insects to the environment ( Lu et al, 2001 ; Douglas, 2009 ), which may also increase the difficulty of A.suturalis control. There are currently few studies examining the symbiotic bacteria of A. suturalis , making the number and species of the symbiotic bacteria in A. suturalis uncertain ( Luo et al, 2021 ; Ma et al, 2021 ). Therefore, it is necessary to investigate the distribution of symbiotic bacteria at different stages of A. suturalis , which will provide a framework for exploring the function of symbiotic bacteria and pest control in A. suturalis .…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese pine sawyer beetle, Monochamus alternatus infected with the entomopathogenic fungus Metarhizium anisopliae, several differentially expressed unigenes were CTLs [51]. Twelve CTL genes were identified in Adelphocoris suturalis (Hemiptera: Miridae) immune responsive genes against fungal and bacterial pathogens [52]. Fourteen CTLs were identified in immunity-related genes in Ostrinia furnacalis against entomopathogenic fungi [53].…”
Section: Discussionmentioning
confidence: 99%
“…Three time points were selected to collected samples, first day, time to reach 10% and 50% mortality. Time to reach 10% and 50% mortality were the time point that the mortality rates of larvae were nearly 10% and 50% ( Ma et al., 2021 ). Considering the dynamics of pathogenicity and lethality in P. aeruginosa , the infected group was sampled at day 1, day 2 (time to reach 10% mortality), day 5 (time to reach 50% mortality) after infection and the H 2 O treatment group was sampled at the same time points as controls.…”
Section: Methodsmentioning
confidence: 99%